What is the frequency of anterior syndesmosis injury in posterior malleolus fracture? - Krzysztof Janik; Dariusz Grzelecki (Journal of Orthopaedic Surgery and Research)
Abstract Background Posterior malleolus fractures may be fixed to restore syndesmosis stability. However, these fractures are often accompanied by ruptures of other ligaments that stabilize the syndesmosis. This study investigates the frequency of anterior syndesmosis injury in posterior malleolus fractures and its effect on rotational stability. Methods Seventy-five consecutive patients who underwent surgery for ankle fractures involving posterior malleolus were prospectively included. Preoperative computed tomography scans in two planes (transverse and sagittal) were used to assess the presence and size of avulsion fractures (LeFort-Wagstaffe and Tillaux-Chaput). Intraoperatively, anterior syndesmosis injuries and rotational stability (determined via the external rotation test) were assessed through direct visualization. Results In 73 patients (97%), a complete injury of the anterior tibiofibular ligament was observed intraoperatively, manifesting as avulsion fractures (8%), ligament injuries (44%), or a combination of both (45%). The mean dimensions of the avulsion fractures were 12.6 mm × 7.5 mm for LeFort-Wagstaffe fractures and 12.4 mm × 7.9 mm for Tillaux-Chaput fractures. Posterior malleolus fractures were stabilized in 57 patients. In 52 of these cases (92%), syndesmosis instability in the direction of external rotation persisted despite fixation of the posterior malleolus. Conclusions Fixation of posterior malleolus fractures is rarely sufficient to fully restore syndesmosis stability. Post-fixation assessment of syndesmosis stability, particularly in external rotation, is essential.